Kreasi Serat Jute Pada Bingkai Cermin Hias Berkonsepkan Eco Friendly Craft - Farida, Siti; Mudjiati (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2023)
Natural fibers are a very prospective commodity to be developed. One of them is jute fiber (Corchorus capsularis), a natural fiber derived from the jute plant from the stem of the plant. Jute trees are perennial plants that grow well in alluvial soils, which are dry, slightly sandy soils in humid tropical climates, one of which is Indonesia. Most of the utilization of jute fiber in Indonesia is only limited as a basic material for making sacks and rug coatings. This research was conducted with the aim of insight into creative creation that has the potential to develop and utilize jute fiber as the main material in the creation of works of art in the form of decorative mirror products by taking the motif structure and adaptation of the macramé technique. The research method uses the concept of practice-based research as a research that begins with research related to preliminary studies of objects and practices, recording and collecting data that are considered important in the creation process. Through exploration, research and practice, jute fiber can produce a product in the form of an ornamental mirror by applying the makramé technique and utilizing natural dyes.